Medication Adherence Rates of Marshallese Patients Treated in a Student-Led Free Clinic - Hudson, Jonell; Balli, Michelle; Purvis, Rachel; Selig, James; Warmack, Thomas; Schulz, Thomas; Coulter, Lois; Peter, Clinton; McElfish, Pearl (Journal of Student-Run Clinics, 2020)
Background: The North Street Clinic is a student-led free clinic providing chronic disease management to the uninsured Marshallese population in Arkansas. Diabetes is a significant health problem for this population with an estimated prevalence of 38% for those living in northwest Arkansas. With a high disease burden, adherence to medication is an important aspect of care. The objective of this study was to measure medication adherence of the North Street Clinic patient population using pharmacy data. Methods: We evaluated medication adherence rates by reviewing pharmacy refill data to calculate proportion of days covered (PDC) for the therapeutic classes of medications most often prescribed in the clinic (diabetes, hypertension, and cholesterol). PDC of 80% or higher is needed for a patient to receive therapeutic benefit from medications within the classes reviewed. Results: The average PDC for each therapeutic class ranged from 52%-55%. Within each therapeutic class, only 20% (19%-21%) of patients had a PDC of 80% or higher that would equate to therapeutic benefit from the medication. Conclusions: Most North Street Clinic patients are not meeting adherence goals to gain therapeutic effect. Future studies are needed in this population to determine exact causes of medication non-adherence and devise interventions to improve adherence. Data can also be used to determine if a program focused on adherence is needed.